Participatory monitoring of the impact of watershed interventions in the tropical Andes - Ochoa,Tocachi BF; Buytaert,W; De,Bièvre B (CRC Press (Taylor & Francis Group), 2017)
This chapter documents the motivations and methods of the Regional Initiative for Hydrological Monitoring of Andean Ecosystems (iMHEA). First, it introduces the context that led to the formation of a diverse consortium of institutions with a joint interest in Andean ecosystems and water. The methodological approach adopted by the monitoring network is then presented in detail. Lastly, this chapter shows preliminary main results, the most relevant milestones and breakthroughs, and the major remaining challenges and perspectives in the scientific, technological and social domains. The objective of the monitoring, as promoted by iMHEA, is to generate standardized data that can be used to increase the knowledge about hydrological ecosystem services in Andean watersheds and the impacts of watershed interventions. The correct use of the generated knowledge, from community level to national governance entities, proves crucial to increase catchment intervention efficiency and improve decision-making on water resources management in data-scarce regions, with potential application to other regions of the world.